A Review of Quantum-Based Diffusion Models in Generative AI - Lima, Glauco; Filatovas, Ernestas; Marcozzi, Marco; Paulavičius, Remigijus (Vilnius University Open Series, 2025)
In recent years, the application of generative AI in several areas has been increasing. Concurrently, quantum computing has been advancing at an accelerated pace, unlocking new possibilities across various fields. This article provides an overview of the integration of quantum computing with generative AI, focusing on diffusion model techniques. We explore use cases documented in recent literature, illustrating how quantum computing techniques, when combined with diffusion models, are being leveraged to drive innovation.